2016
DOI: 10.1037/per0000181
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation between grandiose and vulnerable narcissism.

Abstract: Current literature on narcissistic personality disorder has emphasized a distinction between grandiose and vulnerable narcissism. Some researchers have further suggested that narcissistic persons fluctuate between grandiose and vulnerable narcissism. However, this perception has been confined largely to clinical experience with no systematic research testing the hypothesis. Clinicians and clinical psychology professors in the current study identified 143 persons who fit a description of either a grandiose or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
129
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(150 citation statements)
references
References 45 publications
14
129
5
2
Order By: Relevance
“…Our present study results showed negative relationships between psychopathy/grandiose narcissism and perceived stress, which aligns with previous research reporting that these are related to lower neuroticism (Gore and Widiger 2016). It is likely that features of the Dark Triad, such as lack of empathy and high self-esteem, buffer against stress.…”
Section: Malevolent Personality and Stresssupporting
confidence: 81%
See 3 more Smart Citations
“…Our present study results showed negative relationships between psychopathy/grandiose narcissism and perceived stress, which aligns with previous research reporting that these are related to lower neuroticism (Gore and Widiger 2016). It is likely that features of the Dark Triad, such as lack of empathy and high self-esteem, buffer against stress.…”
Section: Malevolent Personality and Stresssupporting
confidence: 81%
“…This could be interpreted as low perceived stress in social settings (Hare 1985;Jones and Paulhus 2013;Miller et al 2016). This disposition aligns with research showing that psychopathy coincides negatively with stress-related traits such as Neuroticism (Birkás et al 2016b;Gore and Widiger 2016). A concluding but tentative assumption would therefore be that the experience of stress in individuals with high levels of psychopathy is relatively low.…”
Section: Dark Triadmentioning
confidence: 71%
See 2 more Smart Citations
“…Gore and Widiger [46] showed, and this has since been replicated by Hyatt and colleagues [47], that when individuals are selected for matching a description of a grandiose narcissist, not only are they rated high in grandiosity, but their raters also describe bouts or periods where they exhibit vulnerable features. The opposite pattern is not true, consistent with our view that vulnerability reflects non-specific personality pathology.…”
Section: Moving Forward: Studying Dynamic Within-person Processesmentioning
confidence: 89%